Collective efficacy and disorder through the eyes of neighbourhood inhabitants and key informants - Hardyns, Wim (European journal of criminology, 2023)
This study examines the ecological reliability, convergent validity and ecological stability of neighbourhood (dis)organizational processes measured by means of two methods: inhabitant surveys and the so-called key informant analysis technique. Considering that ecological processes play a major role in many contemporary criminological theories and research, it is vital to take into account methodological challenges and to question the reliability, validity and stability of the measures reflecting these underlying processes. (Dis)organizational processes are predominantly measured by means of questionnaires surveying neighbourhood inhabitants. To yield ecologically reliable and valid measures this approach requires large numbers of respondents. In this study we analyse the relationships between ecological measures of neighbourhood processes based on surveys of inhabitants versus key informants. The findings suggest that key informants can provide reliable, valid and stable measures of (dis)organizational neighbourhood processes. Therefore, the key informant analysis technique is an essential complementary, or even substitutive, method in the measurement of neighbourhood processes; shared survey-method variance is eliminated and it is possible to survey fewer key informants than inhabitants to obtain reliable and valid information on social trust and disorder. Nevertheless, this method is not suitable for measuring all neighbourhood processes, such as informal social control. Therefore, outstanding challenges and avenues for future research are discussed as well.